1994
DOI: 10.1002/ajim.4700260111
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among female registered nurses and school teachers in British Columbia

Abstract: The mortality profile of female nurses and teachers in British Columbia (BC) was examined using age-standardized proportional mortality ratios (PMRs) calculated for the period 1950-1984. Lowered overall mortality among nurses was seen for degenerative heart disease and for cerebrovascular accidents. Significantly elevated PMR values were observed for cancer of the breast and ovary in nurses of age 20-65 years. PMRs were significantly elevated for cancer of the pancreas and leukemia among those age 20 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 10 publications
4
33
2
Order By: Relevance
“…occupational status, was related to high risks of breast cancer [17][18][19][20][21] . One of the most consistent results of previous studies was that increased risk of breast cancer was found among women with professional and managerial occupations [21][22][23][24][25][26][27][28] . Increased risk of breast cancer has also been found for specific job titles in this category, particularly nurses and teachers [21][22][23][24][25][26][27] .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…occupational status, was related to high risks of breast cancer [17][18][19][20][21] . One of the most consistent results of previous studies was that increased risk of breast cancer was found among women with professional and managerial occupations [21][22][23][24][25][26][27][28] . Increased risk of breast cancer has also been found for specific job titles in this category, particularly nurses and teachers [21][22][23][24][25][26][27] .…”
Section: Discussionsupporting
confidence: 66%
“…One of the most consistent results of previous studies was that increased risk of breast cancer was found among women with professional and managerial occupations [21][22][23][24][25][26][27][28] . Increased risk of breast cancer has also been found for specific job titles in this category, particularly nurses and teachers [21][22][23][24][25][26][27] . To the best of our knowledge, none of the results in animal experiments showed an increased incidence of mammary tumor induced by trichloroethylene or tetrachloroethylene.…”
Section: Discussionsupporting
confidence: 66%
“…As with breast cancer, the risk of ovarian cancer is influenced by hormones and reproductive factors (31). Confounding by reproductive factors has been suggested to explain earlier findings of an association (32)(33)(34). In our present study, the number of children and age at first birth explained very little of the observed excess of ovarian cancer, and the observed increase according to time since first employment (table 3) may have been due to different and nonoccupational causes.…”
Section: Period Of First Employmentmentioning
confidence: 85%
“…Several studies have found teachers and other professional and managerial employees to have an increased risk for developing breast cancer [Bernstein et al 2002;King et al 1994;MacArthur et al 2007;Pollán and Gustavsson 1999;Rubin et al 1993;Snedeker 2006], but others have not [Calle et al 1998;Coogan et al 1996;Petralia et al 1998]. No causative workplace exposures have been identified for these occupations, and it is postulated that the possible increase in risk is a result of non-occupational risk factors such as parity (number of times a woman has given birth), maternal age at first birth, contraceptive use, diet, and physical activity [MacArthur et al 2007;Snedeker 2006;Threlfall et al 1985].…”
Section: Breast Cancermentioning
confidence: 99%